2022
DOI: 10.3389/feduc.2022.770094
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Accelerating Academic Teachers’ Digital Competence in Distance Teaching

Abstract: This study examines, using a cross-sectional approach, the digital competence of academic teachers at a time when teaching shifted to digital distance learning at the start of the COVID-19 pandemic. Teachers from different academic fields at a large multidisciplinary Finnish university (N = 265) responded to a questionnaire about the purposes for which they use digital tools in teaching, how they evaluated their competence at distance teaching during the lockdown of March-May 2020 and their beliefs about dista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 68 publications
0
24
0
4
Order By: Relevance
“…In recent times there have been numerous studies on digital competence in university education in times of COVID-19. Studies such as García-Prieto et al ( 2022 ), have shown that during this pandemic, university students have developed their level of digital competence, as have the teaching staff (Myyry et al, 2022 ). Recent studies such as those by Reisoğlu & Çebi ( 2020 ) summarizes some of the skills a good teacher must possess to achieve a quality education process with the students: training for technological literacy, communication and collaboration, safety, and the resolution of problems.…”
Section: Theoretical Framework and Related Studiesmentioning
confidence: 99%
“…In recent times there have been numerous studies on digital competence in university education in times of COVID-19. Studies such as García-Prieto et al ( 2022 ), have shown that during this pandemic, university students have developed their level of digital competence, as have the teaching staff (Myyry et al, 2022 ). Recent studies such as those by Reisoğlu & Çebi ( 2020 ) summarizes some of the skills a good teacher must possess to achieve a quality education process with the students: training for technological literacy, communication and collaboration, safety, and the resolution of problems.…”
Section: Theoretical Framework and Related Studiesmentioning
confidence: 99%
“…-Combinar métodos de investigación cuantitativos y cualitativos, y desarrollar nuevos métodos de evaluación (Al Khateeb, 2017;Hämäläinen et al, 2021), como las rúbricas de evaluación (Marcano et al 2020) o la evaluación acompañada de intervención formativa (Miguel-Revilla et al, 2020). -Recoger evidencias de la CDD mediante pruebas competenciales que complementen la propia percepción docente (Viñoles-Cosentino et al, 2021) y que pueden carecer de objetividad (Baena-Morales, 2020; Myyry et al, 2022). -Tener en cuenta factores que afectan en los resultados: factores sociodemográficos, como el género (Esteve-Mon et al, 2020a), los años de experiencia docente (Zhao, 2021), la edad o el nivel educativo (Flores-Lueg & Roig-Vila, 2019), y factores estructurales, como la dotación de recursos o las oportunidades formativas de los docentes (Cattaneo et al, 2022).…”
Section: áMbito De Investigación 3 Análisis De Los Resultados De La E...unclassified
“…La mayor parte de los estudios basados en un enfoque cuantitativo realizan análisis descriptivos, correlacionales (Jorge-Vázquez et al, 2021;Paz Saavedra et al, 2022), inferenciales (Gallego-Arrufat et al, 2019Muñoz y Ruiz-Domínguez, 2021;Pongsakdi et al, 2021), predictivos (Çebi & Reisoğlu, 2020;Guillen-Gamez & Mayorga-Fernandez, 2020;Myyry et al, 2022) y de regresión (Cattaneo et al, 2022;Hämäläinen et al, 2021;Jiménez-Hernández et al, 2020;Muñoz & Ruiz-Domínguez, 2021;Tomczyk, 2021;Tomczyk et al, 2021). Los estudios basados en un enfoque cualitativo se centran en análisis de contenido inductivo y deductivo (Sales et al, 2020;Suárez-Guerrero et al, 2021).…”
Section: áMbito De Investigación 2 Descripción De Los Métodos De Inve...unclassified
“…[ 49 ]. In a high-quality online educational system, universities must constantly support teaching staff during the transition from classic face-to-face learning to online teaching [ 50 , 51 , 52 , 53 , 54 ]. Despite the difficulties in the rapid shift between face-to-face learning and online education, and/or vice versa, universities have made appreciable attempts to ensure that no disruption to learning and the competence flow of teaching-learning processes occurs, imposing fast adaptation to the new situation [ 55 ].…”
Section: Hypothesis and Conceptual Model Developmentmentioning
confidence: 99%